The playing experiences of esports participants: an analysis of hostility and treatment discrimination in esports environments - Darvin, L.; Vooris, R.; Mahoney, T. (Journal of Athlete Development and Experience, 2020)
The esports industry has seen rapid growth over the previous decade with additional opportunities for participants to compete in competitive and casual environments. As such, the sport industry has taken notice of this increase in pop-ularity and exposure for esports. A recent call to arms by sport management scholars suggests that the field of sport management needs to broaden research endeavors to include analyses of esports and esports spaces. To that end, this investigation serves as one of the first that investigates the playing experiences of esports participants, with a particular focus on the presence of discrimination and hostility in playing environments for men and women competitors. Previous events within the esports industry, such as the now infamous harassment of female gamers known as "Gamergate," sug-gest that female esports players may experience discrimination and hostility at higher rates than their male counterparts. Guided by the frameworks of hegemonic masculinity and treatment discrimination, this investigation gauged the experi-ences of men and women esports participants with discrimination and hostility in esports playing environments. Results indicated that female esports participants reported experiencing instances of treatment discrimination more frequently than their male counterparts, while male participants reported experiencing hostility more frequently. Results aim to assist the esports industry as well as sport management scholars in guiding new policy to create inclusive spaces for esports enthusiasts and career hopefuls.